Question 1)
Given: F(x) = 3x^2 + 1, G(x) = 2x - 3, H(x) = x
F(G(x)) = 3(2x - 3)^2 + 1
F(G(x)) =3(4x^2 - 12x + 9) + 1
F(G(x)) = 12x^2 - 36x + 27 + 1
F(G(x)) =12x^2 - 36x + 28
Question 2)
Given: F(x) = 3x^2 + 1, G(x) = 2x - 3, H(x) = x
H -1 (x) = x (inverse)
Answer:
7 degrees colder
Step-by-step explanation:
15 degrees - 8 degrees = 7 degrees
Answer:
C. 3, -7
Step-by-step explanation:
x^2 +4x-21 =0
Factor
What 2 numbers multiply to -21 and add to 4
7*-3 = -21
7-3 = 4
(x+7) (x-3) =0
Using the zero product property
x+7 =0 x-3=0
x+7-7=0-7 x-3+3=0+3
x = -7 x=3
C, a²+b²=c²
why does this have to be 20 characters long
Answer:
C. 3x
Step-by-step explanation:
The first two choices give 1 solution each.
The last choice gives an infinite number of solutions.
Choice C. gives no solution.
3x + 9 = 3x
Subtract 3x from both sides.
9 = 0
Since 9 = 0 is false, equation 3x + 9 = 3x has no solution.
Step-by-step explanation: